A tomato chloroplast-targeted DnaJ protein, SlDnaJ20 maintains the stability of photosystem I/II under chilling stress. (31st December 2022) - Cai, Guohua; Xu, Yujie; Zhang, Shuxia; Chen, Tingting; Liu, Gan; Li, Zhengyue; Zhu, Youshuang; Wang, Guodong
ABSTRACT: DnaJ proteins are key molecular chaperones that act as a part of the stress response to stabilize plant proteins, thereby maintaining protein homeostasis under stressful conditions. Herein we used transgenic plants to explore the role of the tomato ( Solanum lycopersicum ) SlDnaJ20 chloroplast DnaJ protein in to the resistance of these proteins to cold. When chilled, transgenic plants exhibited superior cold resistance, with reduced growth inhibition and cellular damage and increased fresh mass and chlorophyll content relative to control. These transgenic plants further exhibited increased Fv/Fm, P700 oxidation, φRo, and δRo relative to control plants under chilling conditions. Under these same cold conditions, these transgenic plants also exhibited higher levels of core proteins in the photosystem I (PSI) and II (PSII) complexes (PsaA and PsaB; D1 and D2) relative to control wild-type plants. Together these results suggested that the overexpression of SlDnaJ20 is sufficient to maintain PSI and PSII complex stability and to alleviate associated photoinhibition of these complexes, thereby increasing transgenic plant resistance to cold stress.